Imitated Prosodic Fluency Predicts Reading Comprehension Ability in Good and Poor High School Readers - Breen, Mara; Kaswer, Lianne; Van Dyke, Julie A.; Krivokapić, Jelena; Landi, Nicole (Frontiers in Psychology, 2016)
Researchers have established a relationship between beginning readers’ silent comprehension ability and their prosodic fluency, such that readers who read aloud with appropriate prosody tend to have higher scores on silent reading comprehension assessments. The current study was designed to investigate this relationship in two groups of high school readers: Specifically Poor Comprehenders (SPCs), who have adequate word level and phonological skills but poor reading comprehension ability, and a group of age- and decoding skill-matched controls. We compared the prosodic fluency of the two groups by determining how effectively they produced prosodic cues to syntactic and semantic structure in imitations of a model speaker’s production of syntactically and semantically varied sentences. Analyses of pitch and duration patterns revealed that speakers in both groups produced the expected prosodic patterns; however, controls provided stronger durational cues to syntactic structure. These results demonstrate that the relationship between prosodic fluency and reading comprehension continues past the stage of early reading instruction. Moreover, they suggest that prosodically fluent speakers may also generate more fluent implicit prosodic representations during silent reading, leading to more effective comprehension.